Religion and Higher Education Achievement in Europe - Goastellec, Gaele (International Higher Education, 2013)
Although religion has historically been a structuring dimension of higher education systems in Europe, very little research interrogates the contemporary link between religion and higher education. But why should that be done? Building from the European Social Survey data, we show that it helps understanding the roles played by higher education in a given society. Furthermore, it grasps religious belongings as a potential indicator of inequalities, along with ethnic and socio-economic background. It thus underlines the cognitive dimension of inequalities, and calls for a broader taking into account of individual belongings in their analysis.